METODE BERMAIN PERAN UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INDONESIA SISWA THAILAND - Miss Sofeeyah Chesoh; Mutia Febriyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to improve the Indonesian speaking skills of Thai students using role-playing methods in the Matayum 3 Islam Witaya School, Thailand. The research method used was Classroom Action Research (CAR) consisting of two cycles, each going through the planning, implementation, observation, and reflection stages. The study involved 20 Thai students, and data were collected through tests, observations, and documentation. The results showed a quite striking improvement in speaking skills, especially in the aspects of pronunciation, word stress, tone, intonation, rhythm, as well as vocabulary selection and sentence structure. The average student score increased from 54 in the pre-action, to 69 in the first cycle, and reached 85 in the second cycle. In addition, the number of students in the very good category also increased from 0% before the action, to 15% in the first cycle, and 30% in the second cycle. These findings indicate that the use of role-playing methods is effective in improving the speaking skills of Thai students.